2022
DOI: 10.1108/sbr-02-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Does the concept of “creating shared value” make sense for multinational firms?

Abstract: Purpose The paper aims to explore how Porter and Kramer’s “Creating shared value” (CSV) framework supports the multinational corporation’s business model to turn social problems into business opportunities in two contextually different international markets. Design/methodology/approach Conceptually, the paper uses the CSV framework to argue that evaluation of business models in different societal contexts (geographically, culturally and economically) might be able to shed more light on the firm-societal need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…It is supported by a set of integrative theories that focus on the integration of social demand with that of the business and ethical theories that focus on doing the right thing for a better society (Dmytriyev et al , 2021; Garriga and Melé, 2004). The authors extend the perspectives of Nandi et al (2022) and Porter and Kramer (2019) that call for integrating societal concerns into the business model by bringing in the competitive strategy dimensions in the discussion of business sustainability. In doing so, the authors also find support for choosing an integrative approach over an instrumental approach articulated by Pless et al (2021).…”
Section: An Integrated Approach Toward Sustainable Business Model Con...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is supported by a set of integrative theories that focus on the integration of social demand with that of the business and ethical theories that focus on doing the right thing for a better society (Dmytriyev et al , 2021; Garriga and Melé, 2004). The authors extend the perspectives of Nandi et al (2022) and Porter and Kramer (2019) that call for integrating societal concerns into the business model by bringing in the competitive strategy dimensions in the discussion of business sustainability. In doing so, the authors also find support for choosing an integrative approach over an instrumental approach articulated by Pless et al (2021).…”
Section: An Integrated Approach Toward Sustainable Business Model Con...mentioning
confidence: 99%
“…The authors extend the perspectives of Nandi et al (2022) and Porter and Kramer (2019) that call for integrating societal concerns into the business model by bringing in the competitive strategy dimensions in the discussion of business sustainability. In doing so, the authors also find support for choosing an integrative approach over an instrumental approach articulated by Pless et al (2021).…”
Section: Simple Doable Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This database is widely used to conduct literature reviews and extract practical sources such as business opportunities, web articles, blogs, news releases, and case studies (Biancone et al, 2022;Boudlaie et al, 2022;Calandra et al, 2023). Considering the research question, the filter "Business Opportunities" seems adequate for looking forward to new entrepreneurial opportunities using the metaverse (Nandi et al, 2022;Weiss and Nemeczek, 2021).…”
Section: Motivations Research Contexts and Data Selectionmentioning
confidence: 99%
“…Menghwar and Daood (2021) demonstrate that the scholarly use of CSV is gradually increasing, highlighting a meaningful, incremental development. CSV moves away from the reputation-based approach (Beschorner and Hajduk, 2017) and shifts the debate of the impact of business on society from a language of responsibility into that of value (Visser and Kymal, 2015), thus stimulating conceptual perspectives and discussions from scholars who study it in different contexts (Awale and Rowlinson, 2014;Kim, 2018;Islam and Hossain, 2019;Nandi et al, 2022). Indeed, before Hartman and Werhane (2013) criticize CSV, Hartman et al (2011) empirically applied the approach and concluded that true underlying value is created when the resources of all stakeholders are brought together and a sustained synergy occurs.…”
Section: Shared Value For Stakeholdersmentioning
confidence: 99%